OPTIMIZING CHARACTER EDUCATION BASED ON THE HADITH OF RASULULLAH SAW AT SDIT KHAIRUR RAHMAN MEDAN - Ikhlasul Amal Pasaribu; Mawaddah Nasution; Munawir Pasaribu (International Journal of Teaching and Learning, 2025)
Character education plays an important role in shaping the young generation who will determine the direction and success of the nation's development in the future. This study aims to analyze how the strategy of internalizing the hadiths of the Prophet Muhammad SAW shapes the character of students at SDIT Khairur Rahman Medan. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the optimization of character education is carried out through three main strategies: daily hadith habits, teacher role models, and curriculum integration. This strategy has succeeded in instilling character values such as honesty, patience, responsibility, compassion, independence and discipline which are also taken from the hadiths of the Prophet Muhammad SAW.